599 New checkpoints controlling function of cytotoxic lymphocytes infiltrating human carcinoma. (9th November 2020) - Herbstritt, Anna; Noessner, Elfriede; Prinz, Petra; Kadiyala, Mani; Maxwell, Melissa; Yan, Dingxue; Cardia, James; Fricker, Simon
Abstract : Background: Although present in high numbers, T and NK cells appear functionally impaired in the renal cell carcinoma (RCC) tumor milieu, as they cannot be stimulated to degranulation and IFN-γ production. This is in part due to altered regulation of signaling downstream of the T cell receptor (TCR). Increased diacylglycerol kinase alpha (DGK-α) has been observed in T and NK cells from the RCC tumor microenvironment (TME). Ex vivo inhibition of DGK-α by the commercially available inhibitor R59022 was able to restore responsiveness to stimulation. 1 2 Inhibition of DGK-α is reported to also block tumor cell growth and survival. 3 4 Many T cells from RCC additionally express the immune checkpoint Programmed cell Death-1 (PD-1). Interaction of PD-1 with PD-L1 on tumor cells blocks AKT signaling and inhibits T cell function. In the clinic, blocking the PD-1/PD-L1 interaction allows tumor control in some patients; however, the majority of patients do not respond long-term. Since DGK-α acts downstream of PD-1 it may, if overactive, curb T cell function despite PD-1/PD-L1 blockade. Thus, we hypothesize that dual inhibition of PD-1 and DGK α might be required to fully unleash the T cell's potential in the TME.Current DGK-α inhibitors are not suitable for clinical application. Therefore, we investigate alternative means using RNA interference (RNAi) to target DGK-α alone as well as in combination with PD-1. Methods: Knockdown was achieved by RNAi using INTASYL TM compounds, developed by Phio Pharmaceuticals. These compounds incorporate drug-like properties into siRNA, resulting in enhanced uptake with no need for transfection reagents. Efficacy was analyzed on mRNA and protein level by rt-qPCR, flow cytometry and Western Blot. Functional assays include cytotoxicity and cytokine production in tumor-mimicking environments. Results: Using INTASYL TM compounds, silencing of DGK-α was observed in human U2OS osteosarcoma as well as K562 erythroleukemic cells. PD-1 knockdown was achieved in human T cells isolated from peripheral blood mononuclear cells (PBMC). Synergy of DGK-α and PD-1 knockdown is tested in tumor-mimicking in vitro systems using T cell/tumor cell co-cultures at high tumor cell density where T and NK cells become functional suppressed as observed in the TME. Conclusions: Strong activity of specific T and NK cells is necessary for tumor control. Dual targeting of PD-1 and DGK-α may be required to fully enable T and NK cell reactivity in the TME. Self-delivering RNAi technology represents a promising approach to targeting intracellular immune checkpoints such as DGK-α, in addition to PD-1 inhibition. References: Prinz PU, Mendler AN, Masouris I, Durner L, Oberneder R, Noessner E. High DGK-α and disabled MAPK pathways cause dysfunction of human tumor-infiltrating CD8+ T cells that is reversible by pharmacologic intervention. J Immunol 2012 Jun 15;188(12):5990–6000. doi: 10.4049/jimmunol.1103028. Epub 2012 May 9. PMID: 22573804. Prinz PU, Mendler AN, Brech D, Masouris I, Oberneder R, Noessner E. NK-cell dysfunction in human renal carcinoma reveals diacylglycerol kinase as key regulator and target for therapeutic intervention. Int J Cancer 2014 Oct 15;135(8):1832–41. doi: 10.1002/ijc.28837. Epub 2014 Mar 26. PMID: 24615391. Torres-Ayuso P, Daza-Martín M, Martín-Pérez J, Ávila-Flores A, Mérida I. Diacylglycerol kinase α promotes 3D cancer cell growth and limits drug sensitivity through functional interaction with Src. Oncotarget 2014 Oct 30;5(20):9710–26. doi: 10.18632/oncotarget.2344. PMID: 25339152; PMCID: PMC4259432. Yanagisawa K, Yasuda S, Kai M, Imai S, Yamada K, Yamashita T, Jimbow K, Kanoh H, Sakane F. Diacylglycerol kinase alpha suppresses tumor necrosis factor-alpha-induced apoptosis of human melanoma cells through NF-kappaB activation. Biochim Biophys Acta 2007 Apr; 1771(4):462–74. doi: 10.1016/j.bbalip.2006.12.008. Epub 2007 Jan 8. PMID: 17276726.